Community Utilization Strategy To Increase The Number Of Customers For Mattea Social Space - Sipangkar, Harry; Armelia Windasari, Nila (Cv. Syntax Corporation Indonesia, 2023)
Mattea Social Space was founded in May 2021, running under PT. Hita Kreatif Nusantara. Mattea Social Space is a space that has a semi cafe and semi restaurant concept. located on jl. Rawasari Bar. I, DKI Jakarta. The second branch which is being built is located on jl. Raya Pekayon No.10, RT.04/RW.01, Pekayon Jaya, Bekasi City, which has an area of 1515 square meters. Mattea Social Space focuses on the variety of food and drinks sold, the area of the customer's seating area and the concept of a nice place with tropical and industrial themes, with the majority of the area being 60% outdoor, 25% semi-outdoor. and 15% indoors. The problem that Mattea Social Space is currently facing is that there has been a decrease in the number of customers in the last few months, the trend of which has been decreasing since the middle of the year. The purpose of the research is first, to find out the best strategy to increase customers by leveraging the community. Second, to propose an implementation plan for the proposed strategy. The conceptual framework used by researchers in this study is that community marketing and community building will affect brand loyalty, and brand loyalty will ultimately increase the number of customers. This research method uses a qualitative approach with data collection techniques, namely observation and interviews. Data analysis with internal and external analysis as a tool for developing programs and strategies to be implemented. From the results of internal research, it is known that the problem that causes a decrease in customers is because many customers move from their gathering places to other or new places that have a different atmosphere. So Mattea Social Space needs a competitive advantage in areas other than the building without spending a lot of money. The results of the study show that the best strategy to increase customers for Mattea Social Space is to create a Community Ecosystem of Mattea Social Space, where Mattea Social Space becomes a gathering place for many communities to gather and carry out various activities in it by providing certain benefits, then as a supporter, it is also necessary to carry out and routinely schedule employee training programs related to service improvement and product development, and also need to implement and schedule routine maintenance for all areas and equipment owned by Mattea Social Space. Then this is carried out under control by making plans to implement these strategies for one calendar year 2023 as well as the KPI (Key Performance Indicator) for each action.